Implementation of The Role of The National Narcotics Agency in Implementing Rehabilitation for Drug Addicts: Study at BNNK Pematang Siantar - Tuangkus Harianja; Firman Halawa; Yasmirah Mandasari (International Journal of Law, Crime and Justice, 2024)
Narcotics bring benefits if used according to the provisions of applicable laws and regulations and will be detrimental if misused, especially by children. Unfortunately, cases of narcotics abuse are like an iceberg phenomenon that can only be seen at the surface but the real amount is difficult to measure.This research is a descriptive analysis research carried out to reveal the implementation of Law Number 35 of 2009 and Law Number 11 of 2012 regarding criminal acts of narcotics abuse by children in the work area of BNNK Pematang Siantar. The method used is the normative method used in preparing this thesis. The type of research carried out, in terms of its form, is prescriptive research aimed at getting suggestions about what should be done to overcome certain problems. This research explains the role of BNNK Pematang Siantar in tackling narcotics abuse among narcotics addicts in Pematang Siantar City. Implementation of coordination in the preparation of strategic plans and annual work plans in the field of P4GN in the Pematangsiantar City area, Implementation of technical policies in the fields of prevention, community empowerment, rehabilitation and eradication in Pematangsiantar City area, Implementation of legal services and cooperation within the Pematangsiantar City area. The efforts of the Pematang Siantar City National Narcotics Agency in carrying out rehabilitation efforts are by strengthening rehabilitation institutions.